(untitled) (Bangabandhu Sheikh Mujib Medical University Journal, 2016)
Empty Sella refers to the absence or relative absence of the pituitary gland on radiologic imaging of the Sella turcica. This is usually an incidental finding, and as few as 10% patients presents with Hypopituitarism. The authors report a 13.5-year-old boy who presei1ted with short stature and absence of signs of pubertal onset. Hormonal assay showed panhypopituitarism. X-ray left wrist joint showed delayed bone age and finally MRl of the brain revealed empty Sella. Growth hormone replacement therapy was started to increase the height. The boy is now on regular follow up to monitor response to treatment.